Whole‐exome sequencing of a unique brain malformation with periventricular heterotopia, cingulate polymicrogyria and midbrain tectal hyperplasia. Issue 5 (13th December 2012) - Okumura, Akihisa; Hayashi, Masaharu; Shimojima, Keiko; Ikeno, Mitsuru; Uchida, Tomohisa; Takanashi, Jun‐ichi; Okamoto, Nobuhiko; Hisata, Ken; Shoji, Hiromichi; Saito, Akira; Furukawa, Toru; Kishida, Tetsuko; et al.
Abstract : We report a case of an infant with unique and unreported combinations of brain anomalies. The patient showed distinctive facial findings, severe delay in psychomotor development, cranial nerve palsy and seizures. Brain magnetic resonance imaging performed at 5 days of age revealed complex brain malformations, including heterotopia around the mesial wall of lateral ventricles, dysmorphic cingulate gyrus, and enlarged midbrain tectum. The patient unexpectedly died at 13 months of age. Postmortem pathological findings included a polymicrogyric cingulate cortex, periventricular nodular heterotopia, basal ganglia and thalamic anomalies, and dysmorphic midbrain tectum. Potential candidate genes showed no abnormalities by traditional PCR‐based sequencing. Whole‐exome sequencing confirmed the presence of novel gene variants for filamin B ( FLNB ), guanylate binding protein family member 6, and chromosome X open reading frame 59, which adapt to the autosomal recessive mode or X‐linked recessive mode. Although immunohistochemical analysis confirmed the expression of FLNB protein in the vessel walls and white matter in autopsied specimens, there may be functional relevance of the compound heterozygous FLNB variants during brain development.